Chest Drains in Daily Clinical Practice - Kiefer, Thomas (Springer International Publishing : Imprint: Springer, 2017)
This book covers all aspects of successfully treating patients using chest drains, beginning with anatomy and ending with physiotherapy and pain management. The aim of the book is to provide medical professionals with a step-by-step guide to using a chest drain, with specific chapters on indications, kinds of chest drains, catheters, drainage systems, how to insert a chest tube, complications during placement and handling of a chest drain, removing a chest drain, management of the pleural space and post-procedural care. Unlike general thoracic surgery textbooks, this book gives a complete overview of chest drains in clinical practice to ensure the best possible care of patients. .